Trends in prevalence of multi drug resistant tuberculosis in sub-Saharan Africa: A systematic review and meta-analysis. - Baba Maiyaki Musa; Aishatu L Adamu; Najibah A Galadanci; Bashir Zubayr; Chisom N Odoh; Muktar H Aliyu (PLoS ONE, 2017)
Background Multidrug resistant tuberculosis (MDR-TB), is an emerging public health problem in sub-Saharan Africa (SSA). This study aims to determine the trends in prevalence of MDR-TB among new TB cases in sub-Saharan Africa over two decades. Methods We searched electronic data bases and accessed all prevalence studies of MDR-TB within SSA between 2007 and 2017. We determined pooled prevalence estimates using random effects models and determined trends using meta-regression. Results Results: We identified 915 studies satisfying inclusion criteria. Cumulatively, studies reported on MDR-TB culture of 34,652 persons. The pooled prevalence of MDR-TB in new cases was 2.1% (95% CI; 1.7-2.5%). There was a non-significant decline in prevalence by 0.12% per year. Conclusion We found a low prevalence estimate of MDR-TB, and a slight temporal decline over the study period. There is a need for continuous MDR-TB surveillance among patients with TB.